ASSESSING THE CHARACTERIZATIONS OF KETOPROFEN LOADED AND UNLOADED VIRGIN COCONUT OIL (VCO) BASED CREAMY NANOEMULSION - RK, SURAWEERA; HGP, PASANSI; MHF, SAKEENA (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â  Objective: The aim was to analyze the characterization of the formulations prepared with and without ketoprofen in virgin coconut oil (VCO) based emulsions. Methods: The primary emulsions were prepared by magnetic stirring, and the process was continued with high sheer homogenization, aiming for nanoemulsion. The present study evaluated the characteristic properties of emulsions such as; droplets size, pH, viscosity, creaming index and microscopic features. Results: Droplets size falls within the range; 144.9-664.7 nm and pH value was 4.91-5.66. It was noted homogenization process improved the characteristics of the emulsion, mainly droplets size and viscosity. Further, found the incorporation of ketoprofen affects the droplets size of emulsions significantly, this could be due to the amphiphilic nature of drug that can affect the core of the surfactants. Characteristic properties of VCO based emulsions were affected by high shear homogenization and incorporation of drug. Conclusion: Characteristic properties of 2.5% (w/w) ketoprofen loaded 23.60% VCO: 30.53%, Tween 80Â®: 45.87% water creamy emulsion is suitable for topical application. Keywords: Ketoprofen, Virgin coconut oil, Nanoemulsion.